EFEKTIVITAS GEL MADU AKASIA TERHADAP PENYEMBUHAN LUKA SAYAT PADA TIKUS PUTIH - Bimby Irenesia; Teguh Satria; Octariany Octariany (LPPM Universitas Abdurrab, 2023)
Wound is the damage or the loss of body tissue that occurs due to factors that disturb the system of body's protection. These factors include trauma, temperature changes, chemicals, explosions, electric shocks, or animal bites. Honey, the natural food produced by honey bees is known as the oldest traditional medicine that has been used for various types of diseases and wound healing. Several detailed examinations have documented the healthful healing effects of honey on various types of wounds. Wounds treated with acacia honey recovery faster than the other treatments. The hypertonic characteristics and acidic pH of honey are considered to be the main factors which responsible for accelerating the wound healing. Studies indicate that among the four Pakistani honeys, acacia honey was found to be better than Zizipus, Brasicca, and Citrus honey in terms of antimicrobial activity, total sugar, and protein content. In addition, the gel form of honey is able to boost the recovery process due to its moist and cool nature. Research objective to analyzing the effectiveness of acacia honey gel on wound healing in white rats. This research method is eksperimental with randomized posttest only control group design. The results of the study found that giving acacia forest honey gel with a concentration of 80% can significantly improve the wound healing process in the third week.